Finite Element Analysis of One-Way Hollow Plate Capacity with Bamboo Apus and Bamboo Petung - Dani Nugroho Saputro; Arnie Widyaningrum; Agus Maryoto; Thomas Calvin Putro Sasongko (Borneo Engineering : Jurnal Teknik Sipil, 2021)
Design capacity is one of the main parameters in the analysis of concrete slab behavior. In general, bent tests for concrete slab will be tested experimentally in the laboratory. However, it requires a lot of energy, cost, and a long time. For that we need a simulation approach with numerical methods that is the finite element method using ABAQUS program. The test object is a composite structure in the form of a one-way hollow plate with bamboo Apus and Petung as structural reinforcement, the test object is modeled in a 3D solid model with a concentrated load. Furthermore, material will be inputted their properties based on the result of experimental tests. Numerical analysis using ABAQUS shows similar collapse behavior with experimental analysis, yet the result of concrete slab capacity to the ultimate and the deflection indicates a difference in the value of the experimental tests. Tests with numerical and experimental methods, both concrete slab specimens with bamboo apus and petung produce a similar crack pattern, namely flexural shear crack. The maximum stress hollow concrete slab bamboo apus +17.71 Mpa and bamboo petung +23.2 Mpa